2016
DOI: 10.21763/tjfmpc.33433
|View full text |Cite
|
Sign up to set email alerts
|

Oyo State Students and Malaria Management

Abstract: Background: Malaria is a vector-borne infectious disease caused by eukaryotic protist of genus Plasmodium and transmitted by female Anopheles mosquitoes. Those living mainly in the world's poorest countries are at risk of malaria as it is more endemic in the tropical and sub-tropical regions. Malaria spread has been linked to environmental changes, malaria vector dynamics, host immune status and individual or community factors such as the socio-economic status, knowledge of malaria and the protective behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…A well-structured questionnaire which comprised of both open and close ended questions was adopted from a work by Ibrahim, et al 4 The survey questionnaire comprised of three sections which included questions on sociodemographics, knowledge of causes, prevention and management, and practice of malaria prevention and management.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A well-structured questionnaire which comprised of both open and close ended questions was adopted from a work by Ibrahim, et al 4 The survey questionnaire comprised of three sections which included questions on sociodemographics, knowledge of causes, prevention and management, and practice of malaria prevention and management.…”
Section: Methodsmentioning
confidence: 99%
“…4 A study on knowledge, attitude and management practice on malaria in Anambra State Nigeria, revealed that respondents' knowledge on the cause of malaria included overwork, sunlight and oily food. On the choice of drugs, only 50.9% used Artemisinin-based Combination Therapies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations